Functional "Janus" Annulus in Confined Channels. Issue 3 (24th November 2015) - Gao, Pengcheng; Hu, Lintong; Liu, Nannan; Yang, Zekun; Lou, Xiaoding; Zhai, Tianyou; Li, Huiqiao; Xia, Fan
Abstract : Scattered Au 3D nanoparticles form distinct functional regions with an uncovered internal surface in confined channels, named the "Janus" annulus. Electrochemical impedance spectroscopy responses to the variations in DNA self‐assembly and hybridization in the channels decorated by the "Janus" annulus are presented. Single nucleotide mutations are further detected in a linear DNA chain, including terminal base polymorphisms.